Development of A Comprehensive Test for Talent Identification in Chinese Youth Racewalking Athletes - Zhang, Lin; Tongdecharoen, Wisute; Tasnaina, Nopporn (International Journal of Sociologies and Anthropologies Science Reviews, 2024)
Background and Aim: Talent identification forms the foundation of competitive sports. Scientific selection of young people with strong athletic talent and potential to compete in sports training is key to developing high-level athletes and achieving excellent athletic results. Therefore, this study aims to develop a comprehensive test for talent identification in Chinese youth racewalking athletes. Materials and Methods: This is a research and experimental development (R&D) study. There are approximately 300 youth racewalkers in China, and this study is implemented in 115 athletes. The main steps and methods of the study are as follows: (1) Literature review and content analysis, search and sort out the factors related to excellent racewalking performance; (2) Invite 7 experts to fill in the semi-structured questionnaire and form a preliminary draft of the comprehensive test; (3) Invite 21 experts to conduct a Delphi evaluation of the comprehensive test content and revise the comprehensive test; (4) Implement the comprehensive test and analyze the data, select the key test through correlation analysis, and conduct a Test-retest analysis to confirm test reliability; (5) Complete the second round of Delphi evaluation and to construct the final comprehensive test and norms. Results: The final comprehensive test for talent identification in Chinese youth racewalking athletes includes five aspects: anthropometric, physiological, physical fitness, skill, and psychology. The comprehensive test for males included 11 items as follows: (1) Pelvic Width; (2) Thigh Length; (3) Calf Length; (4) VO2 max; (5) 400m Run; (6) 3000m Run; (7) 1000m Racewalking; (8) Sit and Reach; (9) Willpower; (10) Mental Resilience; and (11) Expectation of Winning. The comprehensive test for females included 8 items as follows: (1) Thigh Length; (2) Calf Length; (3) VO2 max; (4) 400m Run; (5) 1000m Racewalking; (6) Standing Long Jump; (7) Willpower; and (8) Motivation to Participate. Conclusion: The holistic evaluation of Chinese youth racewalking athletes encompasses a diverse range of factors, from physical dimensions to psychological attributes, reflecting a nuanced understanding of talent beyond mere physical prowess.